Computational Color Imaging Second International Workshop, CCIW 2009, Saint-Etienne, France, March 26-27, 2009. Revised Selected Papers - Trémeau, Alain; Schettini, Raimondo; Tominaga, Shoji (Image Processing, Computer Vision, Pattern Recognition, and Graphics, 2009)
This book constitutes the thoroughly refereed proceedings of the Second Computational Color Imaging Workshop, CCIW 2009, which was held in Saint-Etienne, France, in March 2009. The 23 revised full papers, presented together with one invited paper, were carefully reviewed and selected from 40 submissions. The papers, which contain a total of 114 colored figures, are oganized in topical sections on computational color vision models; color constancy; color image/video indexing and retrieval; color image filtering and enhancement; color reproduction (printing, scanning, displays); and multi-spectral, high-resolution and high dynamic range imaging.